Continuing professional development and its perceived benefits among midwives (KHD-Production, 2025)
Midwife-nurses in the Cordillera Administrative Region are vital in delivering exceptional care to mothers and newborns. Their continuous professional development is paramount in a rapidly evolving healthcare landscape. This study aimed to understand midwives' experiences with CPD and how it bolsters skills, enhances well-being, and informs effective professional development. This quantitative descriptive study utilized a simple random probability sampling method, surveying 139 midwives in CAR from March to April 2025. A modified and validated survey tool assessed perceptions of CPD benefits. Descriptive and inferential statistics, including F-tests/ANOVA, were performed using SPSS version 20. Most of the 139 study participants were 28–32 years old with 1–5 years of work experience. The perceived benefits of Continuing Professional Development received a high overall average rating (2.53–2.75). Specifically, financial gain and professional network development obtained the highest average rating of 2.75. Midwives generally agreed that CPD positively influences career development and personal skills. While financial income was recognized, career advancement was prioritized over immediate financial gains, viewing CPD as a strategic investment. Enhanced personal competencies were seen as the most direct benefit of CPD—midwives in the Cordillera Administrative Region value CPD for personal growth, career advancement, and networking. Recommendations include designing CPD opportunities emphasizing skill enhancement and career progression to meet their perceived needs, ensuring these vital healthcare providers are equipped for their crucial roles.